2009
DOI: 10.1109/led.2008.2010340
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Thermal Resistance of AlGaN/GaN Electronic Devices Using Novel Nucleation Layers

Abstract: Currently, up to 50% of the channel temperature in AlGaN/GaN electronic devices is due to the thermal-boundary resistance (TBR) associated with the nucleation layer (NL) needed between GaN and SiC substrates for high-quality heteroepitaxy. Using 3-D time-resolved Raman thermography, it is shown that modifying the NL used for GaN on SiC epitaxy from the metalorganic chemical vapor deposition (MOCVD)-grown standard AlN-NL to a hot-wall MOCVD-grown AlN-NL reduces NL TBR by 25%, resulting in ∼10% reduction of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
51
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 18 publications
(23 reference statements)
2
51
0
Order By: Relevance
“…Figure 3(a) shows a two order of magnitude reduction in our measured thermal conductivity relative to that of bulk single crystal AlN measured by Slack. 4 Values of similar magnitude (1 W/mK at 300 K) in AlN films were measured by Dinescu et al 6 and Riedel et al 8 Dinescu et al 6 also observed temperature invariant thermal conductivity from 77 to 300 K (reproduced in Figure 3(a)). Plan view TEM images, shown in Figure 3(b), reveal that the AlN layer has an extremely high threading dislocation density, an effect attributed to its lattice mismatch with the SiC substrate.…”
supporting
confidence: 76%
See 3 more Smart Citations
“…Figure 3(a) shows a two order of magnitude reduction in our measured thermal conductivity relative to that of bulk single crystal AlN measured by Slack. 4 Values of similar magnitude (1 W/mK at 300 K) in AlN films were measured by Dinescu et al 6 and Riedel et al 8 Dinescu et al 6 also observed temperature invariant thermal conductivity from 77 to 300 K (reproduced in Figure 3(a)). Plan view TEM images, shown in Figure 3(b), reveal that the AlN layer has an extremely high threading dislocation density, an effect attributed to its lattice mismatch with the SiC substrate.…”
supporting
confidence: 76%
“…[3][4][5][6] Previous thin film studies have been (i) based on ideal films with low defect concentrations that are unrepresentative of LED grade films 3,7 or (ii) focused on high electron mobility transistors (HEMTs), rather than LED architectures. [8][9][10] Neither submicron GaN films nor real nitride based LED devices have been investigated.Studies of Si and other thin films have demonstrated that thermal conductivity is greatly reduced when the thickness of the film or the defect spacing is less than the intrinsic mean free path of the phonons. 5,11,12 Nitride based LED structures are fabricated from multiple layers of thin films ranging from 3 nm to 100 nm in thickness; whereas, the spectrum-average phonon mean free path in GaN at 300 K is $100 nm, 13 and the longest phonon mean free paths in the spectrum are much greater.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1 HEMTs are essential to high-power and high-speed switching operations that generate heat as a byproduct. 2,3 While thermal packaging is essential to minimize operating temperatures, nearly half of the total thermal resistance comes from the nitride device itself. 2,3 Experiments on bulk nitrides show that thermal transport is phonon-dominated.…”
mentioning
confidence: 99%